Pathophysiology of COVID-19: Everywhere You Look You Will See ACE2! - Cousin, Vladimir L.; Giraud, Raphael; Bendjelid, Karim (Frontiers in Medicine, 2021)
Angiotensin converting enzyme 2 (ACE2) seems to be a central actor in the pathophysiology of SARS-Cov-2 infection. First, it acts as the receptor for the virus and permits its attachment to cells expressing ACE2. Second, the relative deficiency of ACE2 during infection could be linked to several clinical features encountered during the disease, like ARDS and coagulation abnormalities. This study explores the strong link between ACE2 and the majority of risk factors for the severe evolution of COVID-19. It seems that all these risks factors are linked to an increased level of ACE2 and/or imbalance in ACE/ACE2.